(3TQM GdYbGFO GdYVOjIs - (3GdUOjbj, GdOhGfj, LdGd GdOjf, eMeO Hf CSYO J (B918 (3g`s
(3ChdgG (B:s
(3Ydi GdhLhO hGNJdahG aj hbhYg abGd HYVge Efg SjbY dbhdg JYGdi cd TjA gGdc EdG hLggs
(3BNQgG (B:s
(3GdbOQI GdeDKQI GdbQjHI aj GdWGYI GdJj gj eY GdaYd ceG gh ePgHg ef Cf GdbOQI eY GdaYd hgh Ydi eG YQag HYV GdeJCNQjf LYd GdCSHGH ehGabI ddeSHHs
(3fSNI efbhdI Yf fSNI GdeDda eDQNI H SfI (B905 (3g` HHdOI LQhfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6 / 32s
(3eYLe GdeDdajf (B3/ 126s
(3cTa GdXfhf (B2 / 1144s
(3TPQGJ GdPgH (B8 / 160s
Keywords: (3GdJhMjO hGdedd hGdfMds